Respuestas

2013-06-13T19:36:24+02:00

3x-y=12    - (3)    luego se van los 3y por lo q sus signos son diferentes
5x-3y=8    (1)               -4x= - 28
-9x+3y= - 36                   x=7              luego hallamos y
5x-3y=8                                      5x-3y=8
                                                   5(7)-3y=8
ojala te sirva                                  35-3y=8
                                                      -3y=8-35
                                                          y= -27/-3
                                                             y= 9